Estructura da familia e motivo de realizado - Angelini, Hebe R. C. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Part of the data from McClelland’s et al, study on the achievement motive in Brasil was re-examined to verify existing relationships between the M.P.A.M. (Projective Method of Evaluation of Motivation) scores and the subject’s family size and birth order. A comparison between the intensity of the achievement motive in 180 adolescents of Sao Paulo and size of their families indicated that the larger the size of the family, the weaker the achievement motive even though the differences were statistically non-significant. The results showed that elder children’s scores were significantly higher than younger children’s on the M.P.A.M. The same results were obtained with only children when compared to children in the middle position and to younger children, i.e., the only children had significantly higher scores.